La nature du déclin économique de la région de Montréal - Chung, Joseph (L'Actualité économique, 1974)
AbstractThere are definitely signs of economic difficulties in the Montreal area. The growth of population, the rate of unemployment, the productivity of its manufacturing industries, the exodus of head offices of major financial institutions and corporations and several other key indicators of economic growth suggest that the Montreal area has been going through a profound economic malaise. The basic question one might raise is whether such economic difficulties reflect a secular stagnation or merely a cyclical recession. This paper is addressed to this question.This paper's thesis is that economic difficulties and the loss of economic supremacy of Montreal are not a matter of cyclical recession and that they are the consequences of a secular stagnation which began as early as 1970's. Started originally by fur and wheat trade and, later, by the trade of iron ore and other minerals, stimulated by railroad and telecommunications, Montreal largely dominated Toronto until 1920's. However, during the decades that followed, while Toronto was taking advantage of the westward shift of economic frontiers in the United States and was rapidly adopting its economy to changing economic conditions, Montreal was unable to readjust its industrial structure to new market and technological requirements. As a result, Montreal has been loosing its traditional market in the West as well as in the Atlantic provinces and the economic gap between Toronto and Montreal in favor of the former has been widening ever since. This is illustrated well by the evolution of the value of building permits.In short, recent economic difficulties in the Montreal area reflect a secular stagnation of its economy and are not the result of a cyclical recession. In light of these considerations, it is clear that needed remedies require something much more then policies applied so far by the government.